2023
DOI: 10.3324/haematol.2022.282528
|View full text |Cite
|
Sign up to set email alerts
|

<i>TET2</i> mutational status affects myelodysplastic syndrome evolution to chronic myelomonocytic leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Associated to this phenotypic feature, more recent studies demonstrated that this MDS subset is characterized by bi-allelic TET2 inactivation (Quang et al, 2023) such as OM-CMML (Calvo et al, 2022). All these data revisit the boundaries between MDS and MDS/MPN.…”
Section: Feasibility On Bone Marrow Samplesmentioning
confidence: 77%
See 4 more Smart Citations
“…Associated to this phenotypic feature, more recent studies demonstrated that this MDS subset is characterized by bi-allelic TET2 inactivation (Quang et al, 2023) such as OM-CMML (Calvo et al, 2022). All these data revisit the boundaries between MDS and MDS/MPN.…”
Section: Feasibility On Bone Marrow Samplesmentioning
confidence: 77%
“…These patients share typical features of CMML and CMML-related molecular features, such as TET2 and SRSF2 mutations and some have prominent bone marrow monocytosis (Geyer et al, 2017;Schuler et al, 2018;Valent et al, 2019). Both recent classifications, the fifth revised WHO classification (Khoury et al, 2022) and ICC (Arber et al, 2022), have lowered this historical threshold (Bennett et al, 1976) into genuine CMML (Quang et al, 2023;Selimoglu-Buet et al, 2017).…”
Section: Feasibility On Bone Marrow Samplesmentioning
confidence: 99%
See 3 more Smart Citations